2001
DOI: 10.1097/00005344-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Modulates Arginine Vasopressin-Mediated Regulation of Renal Function

Abstract: Taurine has been implicated in the regulation of arginine vasopressin (AVP) secretion, and we have previously shown altered renal excretory function in the taurine-depleted rat. To further elucidate the role of taurine in AVP-mediated renal responses, the effects of an antagonist for renal AVP receptors were examined in four groups of conscious rats: control, taurine-supplemented, taurine-depleted, and taurine-repleted. Control and taurine-supplemented rats displayed similar and significant AVP receptor antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In addition, taurine is known to be an important modulator and regulator of renal function, and it contributes to body-fluid and electrolyte homeostasis. This suggests a critical role for taurine in renal IR injury [ 27 , 28 ]. Like to taurine, the most important physiological roles for betaine are as an osmolyte and a methyl donor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, taurine is known to be an important modulator and regulator of renal function, and it contributes to body-fluid and electrolyte homeostasis. This suggests a critical role for taurine in renal IR injury [ 27 , 28 ]. Like to taurine, the most important physiological roles for betaine are as an osmolyte and a methyl donor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase of urea transport can be due to enhanced release of vasopressin which is known to stimulate urea transport [36]. In taurine-depleted rats, the plasma vasopressin level was significantly higher than in the control rats leading to the production of hyperosmolar urine [29]. Thus, increased vasopressin concentrations and stimulation of urea transport may maintain urinary concentrating ability despite the lack of one of the organic osmolytes.…”
Section: Discussionmentioning
confidence: 99%
“…; total of 90 minute post-infusion collection) were determined in pre-instrumented conscious animal. 3 H-Inulin was used for measurement of the glomerular filtration rate (GFR) [ 18 - 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…These include its purported antioxidant, membrane stabilizing, cellular osmoregulatory and antiapoptotic effects [ 14 - 17 ]. In addition, we have shown that taurine is an important modulator/ regulator of renal function and therefore a contributor to body fluid and electrolyte homeostasis [ 18 - 21 ]. Thus we conjectured that body taurine status is an important determinant of the outcome of renal IR injury.…”
Section: Introductionmentioning
confidence: 99%